Peroral endoscopic myotomy: a meta-analysis - Akintoye, Emmanuel; Kumar, Nitin; Obaitan, Itegbemie; Alayo, Quazim A.; Thompson, Christopher C. (Endoscopy, 2016)
Background and study aim: Peroral endoscopic myotomy (POEM) is a relatively novel minimally invasive technique that is used to treat achalasia and other esophageal motility disorders. We systematically reviewed the medical literature in order to evaluate the safety and efficacy of POEM. Methods: We performed a comprehensive review and meta-analysis of studies published up to March 2016 that reported on clinical outcomes of POEM. Five databases were searched: MEDLINE, EMBASE, Ovid, CINAHL, and Cochrane.Results: A total of 36 studies involving 2373 patients were included in the review. Clinical success (Eckardt score ≤ 3) was achieved in 98 % (95 % confidence interval [CI] 97 % – 100 %) of patients after the procedure. The mean Eckardt score decreased from 6.9 ± 0.15 preoperatively to 0.77 ± 0.10, 1.0 ± 0.10, and 1.0 ± 0.08 within 1, 6, and 12 months of treatment. In addition, there were significant decreases in the average lower esophageal sphincter pressure, integrated relaxation pressure, and the average heights of the barium column following a timed barium esophagogram after the procedure. After a mean follow-up of 8 months post-procedure, the rates of symptomatic gastroesophageal reflux, esophagitis on esophagogastroduodenoscopy, and abnormal acid exposure were 8.5 % (95 %CI 4.9 % – 13 %), 13 % (95 %CI 5.0 % – 23 %), and 47 % (95 %CI 21 % – 74 %), respectively.Conclusions: POEM appears to be safe and effective based on the large body of current evidence, and warrants consideration as first-line therapy when an expert operator is available.